Bangeni, B & Kapp, R. (eds.). 2017. Negotiating Learning and Identity in Higher education: Access, Persistence and Retention. London & New York: Bloomsbury. - Peter Looker (University of Johannesburg, 2018)
Peter Looker finds that student voice comes through very strongly in Negotiating Learning and Identity in Higher education: Access, Persistence and Retention, which focuses on the pathways of black working-class, first-generation, tertiary students. The book is a volume of the Bloomsbury series 'Understanding Student Experiences in Higher Education'. How to cite this book review: LOOKER, Peter. Book review: Bangeni, B & Kapp, R. (eds.) 2017. Negotiating Learning and Identity in Higher education: Access, Persistence and Retention. London & New York: Bloomsbury. Scholarship of Teaching and Learning in the South v. 2, n. 2, p. 92-94, Sept. 2018. Available at: http://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=81&path%5B%5D=28 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/